PEMANFAATAN ROTAN SEBAGAI BAHAN KERAJINAN ANYAMAN DI DESA SEDAHAN JAYA KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Simanjuntak, Natalia; Idham, M.; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2016)
Rattan is one of the non-timber forest products that is very potential and has been widely used by the community, among others for weaving materials, ropes, or other purposes. Many types of rattan have been used by the community for various purposes, but to date, it has not been known what types of rattan are used by the people in Sedahan Jaya Village and how the traditional wisdom of the community is in using rattan. This research aims to find out the types of rattan used as material for woven handicrafts and the traditional wisdom in using rattan among the community of Sedahan Jaya, Sukadana Subdistrict, North Kayong Regency. The findings showed that people in Sedahan Jaya village used 10 types of rattan for the materials of making woven crafts, and produced 12 kinds of crafts. Keywords: Utilization, rattan, weaving materials.